Peningkatan Literasi Digital di SDN 02 Tualang - Akhmad suyono; Merlina Sari; Fitri Wulandari; Sari Tri Ningsih (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The development of science and technology has brought major changes to human literacy in the world, including Indonesia. The internet is a result of the development of science and technology which not only provides entertainment but also information and literacy for its users. This makes the internet a human necessity in everyday needs. As previously explained, the problems faced by the internet generation are this generation's vulnerability to pornographic content; vulnerable to being encouraged to participate in spreading hate speech; vulnerable to being involved in cyber crime; vulnerable to plagiarism in completing learning assignments at school; vulnerable to exposure to terrorism and radicalism; the rise of cyber bullying among the Internet Generation; and vulnerable to being involved in spreading fake news (hoaxes). In guiding the Internet Generation in using the internet wisely to prevent the negative impacts of internet use in high school, digital literacy outreach can be implemented. For this reason, we offer the "Digital Literacy Socialization" activity. Through this socialization activity, it is hoped that we can increase the insight and knowledge of the Internet Generation in using the internet in a way that benefits themselves and does not harm others based on the ITE Law.